Cocoa farmers' characteristics on climate variability and its effects on climate change adaptation strategy - I. Idawati; N.A. Sasongko; A.D. Santoso; M. Septiani; T. Handayani; A.Y.N. Sakti; B.D. Purnamasari (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Climate change has a greater influence on agriculture through local climate variability than global climate patterns. The impact of climate change on agricultural productivity and shifts in crop patterns varies significantly across regions. Its impact is closely tied to the technical abilities of farmers in managing their cocoa farming businesses. Technical skills encompass the proficiency of farmers in adopting adaptive cocoa cultivation techniques for planting, maintaining cocoa plants, as well as handling harvest and postharvest processes. The technical capability is interconnected with factors such as crop dependency on rainfall patterns, availability of infrastructure for quality inputs, soil degradation and fertility, nutrient levels, limited farmers’ resources, and technology penetration. Given the significant impact of climate change on cocoa farmers, it becomes crucial to enhance their adaptive capacity to address these challenges. Therefore, this study aimed to analyze the relationship between the characteristics of farmers and their adaptive capacity in responding to the impact of climate change.METHODS: Data were collected from 960 populations from two regencies, 4 districts, and 8 villages using the stratified sampling technique through interviews with 282 respondents. The sample size was determined using the Slovin formula through in-depth interviews with five key informants. The data collected were descriptively and statistically analyzed using the Excel program, which involved generating frequency distribution tables. Furthermore, the Mann-Whitney test, utilizing Statistical Product and Service Solution version 24, was employed to conduct a comparative analysis.FINDINGS: This result showed that the characteristics of farmers in the two areas were relatively the same in terms of age, non-formal education, number of family dependents, and perceptions of the climate. In terms of age, most farmers fell within the mature group of 36-48 years, with an average age of 44.63, considering in low category. The low productive age of farmers (44.63), along with their non-formal education, including training in climate field schools and integrated pest management field schools, as well as the number of dependents and their perceptions of climate change, emerged as significant parameters impacting farmers'''' decision-making processes. These factors also influenced their ability to cope, adapt, and seek new approaches to manage and mitigate the effects of climate change on their farming operations.CONCLUSION: The relationship between farmers’ characteristics and adaptive capacity showed that the larger the land owned by farmers, the higher the managerial adaptability of farmers with lower technical ability.